(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the content of the global preschool education system, modern approaches, advanced practices and methodologies used in practice to ensure the comprehensive development of children, and their impact on the educational process. The experiences and methodologies of developed countries around the world, the results of ongoing research, and current studies related to children’s cognitive abilities, physical development, psychological development, social and emotional development, speech development, artistic and creative development, as well as their formation as individuals in further education and life, are discussed in detail.